Risco e vulnerabilidade como analisadores nas políticas públicas sociais: uma análise crítica - Benelli, Silvio José (Programa de Pós-Graduação em Psicologia, Pontifícia Universidade Católica de Campinas, 2016)
Abstract A critical overview of the historical journey and the process of institutionalization of social assistance as a public policy are presented. The discourse about the social risk involved in it and in the national policy for children and adolescents is also addressed for the analysis of the normalizing possibilities of Psychology and Social Care. In order for Social Assistance, including psychologists, to find effective solutions for social problems, it has to be - from the very beginning -, based entirely on the ethical statement, which should manage its effects on citizens as subjects of rights.

Resumo É apresentada uma síntese crítica sobre o percurso histórico e o processo de institucionalização da Assistência Social como política pública; além disso toma-se o discurso sobre o risco social presente nela e também na política nacional para crianças e adolescentes como analisador das possibilidades normalizadoras da Psicologia e da Assistência Social. Para que a Assistência Social, incluindo-se os psicólogos, possa buscar um efetivo equacionamento do problema social, é preciso que se paute radicalmente - logo de início -, pelo enunciado ético que deve orientar seus efeitos: o sujeito cidadão de direitos.
Risk and vulnerability as criteria to evaluate social and public policies: A critical analysis
Keywords: Social assistance; Institutional evaluation; Public policies; Psychology, Social; Assistência Social; Avaliação institucional; Políticas públicas; Psicologia social